Родинна обрядовість поліщуків (За матеріалами експедиційного дослідження) - Боряк, О. (Народна творчість та етнографія, 2007)
The author analyzes the fieldwork evidence concerning magical rites that accompanied so called rites of passage – birth, wedding and death. This material was fixed in 2006 in 10 villages in the Northern part of Rivnenske Polissya ethnografic zone. The region is well known for integrity of its main archaic features. The author introduces main ritual terms, forms of implementation and attributes of the key life cycle events.